Neues Musikalisches Seelenparadies Neuen Testaments (1662): Johann Rist/Christian Flor ; kritisch herausgegeben und kommentiert von Johann Anselm Steiger ; kritische Edition des Notentextes von Oliver Huck und Esteban Hernández Castelló - Flor, Christian (Neudrucke deutscher Literaturwerke, 2017)
The work, critically edited for the first time with commentary, is Rist's ninth collection of sacred songs, and an extraordinary document of early modern poetry based on biblical texts from the New Testament. Along with 82 songs about New Testament texts, the volume includes many dedicatory pieces that reveal Rist's scholarly network. Christian Flor composed the musical scores